The Association of South East Asian Nations (ASEAN) Efforts to Approve Myanmar Transitional Government Proposal on ASEAN 2014 Chairmanship - Manurung, Hendra (Universitas Muhammadiyah Yogyakarta, 2015)
In 2011, Myanmar proposed to take the 2014 Chairmanship by swapping their turn with Laos. This is a deviation to ASEAN Charter Article 31 which says that the Chairmanship of ASEAN shall rotate annually based on the alphabetical order of the English names of Member States. Fortunately, by default, Myanmar’s Chairmanship would have to be in 2016 after Malaysia in 2015. Despite this and also considering year 2014 is crucial as it is only a year before the plan of the realization of ASEAN Economic Community on 31st January 2015, ASEAN approved Myanmar’s 2014 Chairmanship proposal. Thus, this research aims to examine the reasons what was ASEAN motives to support Myanmar Democratic Reform, and how ASEAN implements its efforts to initiate Myanmar for ASEAN 2014 Chairmanship. In conducting the research, the writer elaborated constructivism theory and institutional approach from international organization theory, which are used as theoretical framework. Through theory of constructivism, the ramification of past events is analyzed. The analysis is conducted particularly by identifying series of events and change of circumstance that affects ASEAN, Myanmar, and other state actors involved. This is done to identify possible factors affecting ASEAN’s decision to approve Myanmar’s 2014Chairmanship proposal. Meanwhile, through institutional approach from international organization theory, the ASEAN Charter is used as a guide to analyze the basis of ASEAN’s assessment of the eligibility of Myanmar’s Chairmanship. ASEAN Charter Article 32 as stated the role of the chairman is the particular article which is used in this research as ASEAN’s standard of procedures (SOP) in assessing Myanmar’s eligibility.